2013
DOI: 10.1557/opl.2013.258
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Recycling of Post-Consumer Plastic Waste in Rural Areas

Abstract: Although the environmental benefits of recycling plastics are well established and most geographic locations within the U.S. offer some plastic recycling, recycling rates are often low. Low recycling rates are often observed in conventional centralized recycling plants due to the challenge of collection and transportation for high-volume low-weight polymers. The recycling rates decline further when low population density, rural and relatively isolated communities are investigated because of the distance to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 18 publications
1
52
0
Order By: Relevance
“…The embodied energy of the solar PV system is estimated by the PV module area, and the energy consumption to produce the PV system in unit size is also determined from prior LCA studies. A previous study investigating a horizontal AC-powered recyclebot found that the energy required for producing a filament is low (8.74 MJ to produce 1 kg HDPE filament) compared to the production from virgin resin (76.7 MJ/kg) and waste HDPE processed in a conventional recycling center (48.9 MJ/kg) [25]. It should be noted that the energy required during the extrusion differs with thermoplastic materials and insulation used on a particular recyclebot machine.…”
Section: Energy Payback Timementioning
confidence: 99%
See 1 more Smart Citation
“…The embodied energy of the solar PV system is estimated by the PV module area, and the energy consumption to produce the PV system in unit size is also determined from prior LCA studies. A previous study investigating a horizontal AC-powered recyclebot found that the energy required for producing a filament is low (8.74 MJ to produce 1 kg HDPE filament) compared to the production from virgin resin (76.7 MJ/kg) and waste HDPE processed in a conventional recycling center (48.9 MJ/kg) [25]. It should be noted that the energy required during the extrusion differs with thermoplastic materials and insulation used on a particular recyclebot machine.…”
Section: Energy Payback Timementioning
confidence: 99%
“…Solar PV growth has been rapid and by 2018, the worldwide PV capacity is predicted to double to 430 GW [59]. As the AC recyclebot extrusion of an HDPE filament requires 21.13 W power, the initial heating needs 0.06 kWh [25]. In this project, it was assumed that the DC recyclebot would use approximately the same power for initial heating, so two small monocrystalline silicon solar modules were used in the design of the system.…”
Section: Solar Photovoltaic Systemmentioning
confidence: 99%
“…It is evident that in Latin America the culture of recycling is starting in the urban areas, while the process of appropriate management of organic and inorganic wastes is incipient in the countryside. Academic literature on the experiences of the recycling process in Latin American rural areas is scarce and just some systematised examples are remarkable (KREIGER, ANZALONE, MULDER, GLOVER & PEARCE, 2013). Regarding this problem in Mexico, it is important to note that there is a public policy, which aims to gather a significant amount of plastic containers of agrochemicals.…”
Section: Breaking and Convergence Pointsmentioning
confidence: 99%
“…In addition, recent work has shown home-based 3-D printing is economically attractive, enabling individuals to fabricate an exponentially growing list of free and open-source designs of products to meet their own needs (Wittbrodt, et al, 2013). Preliminary analysis also indicates distributed manufacturing with 3-D printing could reduce the environmental impact attributed to manufacturing household goods primarily by reducing transportation related embodied energy, but also by reducing the quantity of material used (Kreiger, et al, 2013;Kreiger and Pearce, 2013a). Recent sales figures in the developed world indicate that personalized or desktop manufacturing with 3-D printers is a growing trend (Economist, 2012;Blua, 2013;Make, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Even the cost of raw plastic is considerable compared to what could be done with recycled waste plastic filament. The commercial filament cost is now 500 times the energy costs of recycling filament (Kreiger, et al, 2013;Kreiger et al, 2014). 4) A number of designs for filament extruders and recyclebots (waste polymer desktop extruders) have been developed, which can produce useable filament from recycled post-consumer plastic including open-source tools using the recyclebot name, Filabot, Filstruder and Lyman Extruder (Baecheler, et al 2013;Kreiger and Pearce, 2013;Kreiger et al, 2014;Filabot, 2012;Lyman, 2012;Elmore, 2013;Thompson, 2012;Douglass, 2013).…”
Section: Introductionmentioning
confidence: 99%